Effectiveness of seasonal inactivated influenza vaccination in Japanese schoolchildren: an epidemiologic study at the community level. Issue 2 (1st February 2020) - Kuniyoshi, Yasutaka; Obara, Taku; Ishikuro, Mami; Matsubara, Hiroko; Nagai, Masato; Murakami, Keiko; Noda, Aoi; Kikuya, Masahiro; Kure, Shigeo; Kuriyama, Shinichi
ABSTRACT: Influenza vaccination is the most effective method for preventing influenza virus infection. The incidence of influenza is higher in schoolchildren than other age groups. This study evaluated the effectiveness of seasonal inactivated influenza vaccination (IIV) in a community population of schoolchildren during two seasons. This study was a cross-sectional survey of public schoolchildren based on data collected in the 2012/2013 and 2014/2015 seasons. The questionnaire was distributed to all public schoolchildren of target grade in a survey area, and 7945 respondents were included in the analysis. The vaccination status and influenza onset were defined based on the self-reported questionnaire by parents or guardians. Generalized linear mixed models were used to adjust clustering within schools and individual covariates and calculate odds ratios (ORs) and 95% confidence intervals (CIs) for associations between vaccination status and influenza onset. The influenza incidence was higher in the 2015 than the 2013 survey (25% versus 17%), although the vaccination rates were comparable between the two seasons. Receiving one- or two-dose vaccination was more protective against influenza than non-vaccination in both the 2013 (OR, 0.77; 95%CI, 0.65–0.92) and 2015 (OR, 0.88; 95%CI, 0.75–1.02) surveys. Full vaccination was also more protective in both the 2013 (OR, 0.75; 95%CI, 0.62–0.89) and 2015 (OR, 0.86; 95%CI, 0.74–1.00) surveys. Seasonal IIV was protective against influenza for Japanese schoolchildren in a community-based real-world setting. The difference in clinical effectiveness of IIV between the two seasons was likely due to the antigenic mismatch between the circulating and vaccine strains.